HUBUNGAN SARAPAN PAGI DAN MAKANAN SELINGAN DENGAN STATUS GIZI PADA ANAK SEKOLAH DASAR DI SD SINGOSARI DELI TUA - Barus, Dewi Tiansa; Purba, Rentawati; Ginting, Daniel Suranta; Aritonang, Dwi Putri (Jurnal Penelitian Keperawatan Medik, 2025)
Nutritional status among elementary school children is influenced by breakfast habits and snack consumption. This study aimed to determine the relationship between breakfast habits and snack consumption with the nutritional status of elementary school children at Singosari Elementary School, Deli Tua. A cross-sectional design was used with 64 respondents selected through proportional random sampling. Data were collected using a 24-hour food recall questionnaire and a Semi Quantitative Food Frequency Questionnaire (SQ-FFQ), while anthropometric measurements were conducted to determine nutritional status based on the BMI-for-age indicator according to WHO standards. The results showed that most children had good breakfast habits (≥4 times per week) and were predominantly categorized as overweight. The Chi-Square test indicated a significant relationship between breakfast habits and nutritional status (p = 0.004) and between snack consumption and nutritional status (p = 0.003). It can be concluded that breakfast and snack consumption are associated with the nutritional status of elementary school children, where the quality of breakfast and the types of snacks consumed play an important role in preventing overweight among school-aged children.